2016
DOI: 10.1007/s00167-016-4408-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between injury patterns of medial patellofemoral ligament and vastus medialis obliquus after acute first-time lateral patellar dislocation

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 38 publications
1
27
2
Order By: Relevance
“…In a two-year follow-up research, MPFL reconstructive surgery without VMO combined repair had no signi cant effect on the re-dislocation in patients with primary patella dislocation compared with conservative treatment (36), this suggested that MPFL reconstruction combined with VMO repair may produce better postoperative outcome. Zhang et al (20) also suggested that more attention should be paid to VMO, that the patients with complete femoral-side injury in particular. Hence, in the preoperative evaluation, the orthopaedic surgeon should carefully assess the injury conditions of MPFL and VMO, then individualized treatment should be adopted for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a two-year follow-up research, MPFL reconstructive surgery without VMO combined repair had no signi cant effect on the re-dislocation in patients with primary patella dislocation compared with conservative treatment (36), this suggested that MPFL reconstruction combined with VMO repair may produce better postoperative outcome. Zhang et al (20) also suggested that more attention should be paid to VMO, that the patients with complete femoral-side injury in particular. Hence, in the preoperative evaluation, the orthopaedic surgeon should carefully assess the injury conditions of MPFL and VMO, then individualized treatment should be adopted for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The VMO elevation was measured on sagittal and coronal planes according to Zhang et al' s (20) measurement method. Brie y, the adductor tubercle could clearly be seen in the transverse slice was de ned as the optimally measurable slice, indicated by the blue line ( Fig.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…Patients were eligible for inclusion if they had suffered an acute, first-time LPD regardless of the injury mechanism. The inclusion criteria were as follows ( 17 18 19 20 21 ):…”
Section: Methodsmentioning
confidence: 99%
“…Using the diagnostic classification criteria from studies of Zhang et al and Balcarek et al ( 17 18 19 20 21 22 23 24 ), the degrees of MPFL injury were divided into partial and complete tears. The manifestations of a partial MPFL tear were defined as thickening and irregularity of the contour, including discontinuity of normal fibers, and intraligamentous or extensive periligamentous edema.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation